Report of National Brain Tumor Society roundtable workshop on innovating brain tumor clinical trials: building on lessons learned from COVID-19 experience. Issue 8 (2nd April 2021) - Lee, Eudocia Q; Selig, Wendy; Meehan, Clair; Bacha, Jeffrey; Barone, Amy; Bloomquist, Erik; Chang, Susan M; de Groot, John F; Galanis, Evanthia; Hassan, Islam; Kalidas, Chitkala; Khasraw, Mustafa; et al.
Abstract: On July 24, 2020, a workshop sponsored by the National Brain Tumor Society was held on innovating brain tumor clinical trials based on lessons learned from the COVID-19 experience. Various stakeholders from the brain tumor community participated including the US Food and Drug Administration (FDA), academic and community clinicians, researchers, industry, clinical research organizations, patients and patient advocates, and representatives from the Society for Neuro-Oncology and the National Cancer Institute. This report summarizes the workshop and proposes ways to incorporate lessons learned from COVID-19 to brain tumor clinical trials including the increased use of telemedicine and decentralized trial models as opportunities for practical innovation with potential long-term impact on clinical trial design and implementation.